2009
DOI: 10.1016/j.jcv.2009.02.001
|View full text |Cite
|
Sign up to set email alerts
|

HPV genotypes in women with squamous intraepithelial lesions and normal cervixes participating in a community-based microbicide study in Pretoria, South Africa

Abstract: a b s t r a c tBackground: Little is known regarding the human papillomaviruses (HPV) genotypes prevalent in women in South Africa, a country with a high incidence of cervical cancer.Objective: To determine the prevalence and HPV genotypes in women with squamous abnormalities and normal cervixes participating in a community-based microbicide study. Study design: A total of 159 cervical specimens, including 56 specimens from women with abnormal cytology (cases) and 103 randomly selected specimens from women wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 12 publications
(13 reference statements)
2
21
1
1
Order By: Relevance
“…[17] A smaller study (N=153) from our region reported an overall HPV prevalence of 58% using the LA. [18] Snijders et al recommend that to accurately study HPV epidemiology, impact of HPV infection and monitor the efficacy of HPV vaccination programmes, the test with the highest analytical sensitivity possible must be used. [19] This shift toward highly sensitive PCR assays has affected findings in recent epidemiological studies, showing that HPV infections are more widespread than had previously been recognised.…”
Section: Discussion Hpv Dna Prevalence and Age Distributionmentioning
confidence: 99%
See 3 more Smart Citations
“…[17] A smaller study (N=153) from our region reported an overall HPV prevalence of 58% using the LA. [18] Snijders et al recommend that to accurately study HPV epidemiology, impact of HPV infection and monitor the efficacy of HPV vaccination programmes, the test with the highest analytical sensitivity possible must be used. [19] This shift toward highly sensitive PCR assays has affected findings in recent epidemiological studies, showing that HPV infections are more widespread than had previously been recognised.…”
Section: Discussion Hpv Dna Prevalence and Age Distributionmentioning
confidence: 99%
“…[14] The 8 most common hrHPV types found in invasive cervical cancer (16,18,31,33,35, 45, 52, 58) as described by De Sanjose were classified as the 'top 8' .…”
Section: Data and Statistical Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Autores (11) determinaram a prevalência de HPV em 91% dos casos e o HPV de alto risco foi detectado em todas as lesões intraepiteliais de alto grau (HSIL), 69% de lesões intraepiteliais de baixo grau (SIL), 57% de células escamosas atípicas de significado indeterminado (ASCUS) e 86% células escamosas atípicas, onde não é possível excluir uma lesão intraepitelial de alto grau (ASC-H).…”
Section: Cálculo De Tamanho Da Amostraunclassified